COVID-19 across Countries: Situation and Lessons for Pandemic control - Shakya, Dhana Ratna; Thapa, Suraj Bahadur; Kar, Sujit Kumar; Sharma, Vinita; Uchida, Naoki; Ortiz, Miguel Reina; Chapagain, Ghanashyam; Poudel, Chandra Kumar; Bhattarai, Pushpa Raj (Journal of BP Koirala Institute of Health Sciences, 2020)
In the context of rapid worldwide spread of COVID-19 pandemic, many facts and issues are coming up. Some are general across borders while some others specific to particular context. We intend to review situation (condition, trend) and lessons (observations, and messages) from 9 different countries across the continents (in brief as contributed by respective authors). We have, here, the accounts and observations from Nepal, India, Japan (Asia); Norway and United Kingdom (Europe); United States of America (North America), Ecuador (South America), Australia and South Africa. General fact is that all need to maintain social distancing, adequate testing, aggressive contact tracing and treatment along with strategies to limit movements and crowds (e.g. lockdown). This pandemic has again shown that there is no border for disaster and pestilence. Borders are artificial. We all human being and whole world is a single unit. We have certain weaknesses, drawbacks and deficits as well as strengths that we need to understand and positively stand together in the battle against this pandemic.